2013
DOI: 10.1161/hypertensionaha.112.00762
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor–Mediated and Nitric Oxide–Dependent Renal Vasodilator Response to Compound 21 Unmasked by Angiotensin-Converting Enzyme Inhibition in Spontaneously Hypertensive Rats In Vivo

Abstract: Abstract-Angiotensin II type 2 receptor (AT 2 R)-mediated vasodilation has been demonstrated in different vascular beds in vitro and in perfused organs. In vivo studies, however, consistently failed to disclose renal vasodilator responses to compound 21, a selective AT 2 R agonist, even after angiotensin II type 1 receptor blockade. Here, we investigated in vivo whether angiotensin-converting enzyme inhibition, reducing endogenous angiotensin II levels, could unmask the effects of selective AT 2 R stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
2
20
1
Order By: Relevance
“…This suggests that upregulation of renal vascular AT2R in hypertension is associated with a countervailing function opposing the increased AT1R-mediated tonic renal vasoconstriction. 9 Thus, the counter-regulatory function of AT1R and AT2R may occur in the vasculature of hypertensive rodents, as described previously in humans also. 10 This implies the need of AT1R blockade to obtain the therapeutic benefit of AT2R stimulation in the vasculature of hypertensive subjects and indirectly supports the existence of a cross-talk between Ang II receptor subtypes.…”
Section: Hypertensionsupporting
confidence: 52%
“…This suggests that upregulation of renal vascular AT2R in hypertension is associated with a countervailing function opposing the increased AT1R-mediated tonic renal vasoconstriction. 9 Thus, the counter-regulatory function of AT1R and AT2R may occur in the vasculature of hypertensive rodents, as described previously in humans also. 10 This implies the need of AT1R blockade to obtain the therapeutic benefit of AT2R stimulation in the vasculature of hypertensive subjects and indirectly supports the existence of a cross-talk between Ang II receptor subtypes.…”
Section: Hypertensionsupporting
confidence: 52%
“…However, when given in combination with the AT 1 R antagonist, candesartan, C21 lowered arterial pressure in SHRs, 10 which fits with this hypothesis. The possibility also exists that high levels of endogenous AngII may result in significant AT 2 R stimulation and thus limit an additional vasodilator effect of C21 administration, as suggested recently by Brouwers et al 11 Similar to the present study, this group did not identify any significant effect of intravenous bolus doses of C21 on RBF in male SHRs, 11 which may reflect the presence of anesthesia, unlike other studies, 10 although AT 2 Rmediated vasodilatation occurred in anesthetized female SHRs in the current study. Interestingly, during combined angiotensin-converting-enzyme inhibition with captopril to inhibit the endogenous production of AngII, Brouwers et al 11 reported that C21 induced dose-dependent renal vasodilatation in male SHRs in the absence of any change in arterial pressure, thus supporting their proposition that the inhibition of endogenous AngII is required in male SHRs for AT 2 R-mediated vasodilatory responses to be manifest.…”
Section: Discussionmentioning
confidence: 96%
“…- C21 may have an impact on BP, depending upon whether blood pressure measurements are made in conscious or anaesthetised rats, because there are at least two examples of AT2R-mediated reductions in blood pressure in anaesthetised rats of strains/models (SHR, obese Zucker rats), in which in the conscious state blood pressure was not affected by AT2R-stimulation [13,16], while under anaesthesia it was [5,26]. …”
Section: Effects Of Systemic At2r Stimulation On Blood Pressure Controlmentioning
confidence: 99%